2013
DOI: 10.1161/atvbaha.112.301008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Netrin-1 and Unc5b in Atherosclerotic Plaques

Abstract: Objective Hypoxia is intimately linked to atherosclerosis and has become recognized as a primary impetus of inflammation. We recently demonstrated that the neuroimmune guidance cue, netrin-1 (Ntn1) inhibits macrophage emigration from atherosclerotic plaques thereby fostering chronic inflammation. However, the mechanisms governing netrin-1 expression in atherosclerosis are not well understood. In this study, we investigate the role of hypoxia in regulating expression of netrin-1 and its receptor Unc5b in plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 36 publications
3
91
0
2
Order By: Relevance
“…Although recently NTN1 and UNC5B protein have been demonstrated in human atherosclerotic plaques, 15 their association with plaque type and different arterial bed in vivo is lacking.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recently NTN1 and UNC5B protein have been demonstrated in human atherosclerotic plaques, 15 their association with plaque type and different arterial bed in vivo is lacking.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
“…15 Recently, it was shown that coronary endothelial cells normally express NTN1, which potently inhibits migration of monocytes in vitro. 26 Our results of downregulation of NTN1 in advanced plaques are supported by the finding that proatherogenic factors (oscillatory shear stress, proinflammatory cytokines) downregulate NTN1 expression in vitro.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
“…113 The production and secretion of repulsive neuroimmune guidance cues such as netrin-1, ephrin-B, and semaphorins 3A and 3E may contribute to macrophage retention. [114][115][116][117] Hypercholesterolemia also impairs the migration of dermal DCs to regional lymph nodes through generation of platelet-activating factor. 118 Oxidized, but not native LDL, inhibits TLR4-induced peritoneal macrophage efflux into lymphatics and in vitro migration through a process that involves CD36, inactivation of Src homology 2-containing phosphotyrosine phosphatase, sustained activation of focal adhesion kinase, and alteration of cytoskeletal dynamics.…”
Section: Macrophage Proliferation and Dynamics In Atherosclerotic Lesmentioning
confidence: 99%
“…Since the deep intimal region is distant from the circulating blood, it easily becomes hypoxic (Hulten and Levin 2009). Although survival mechanisms are activated in macrophages trapped in such hypoxic areas (Ramkhelawon et al 2013), promotion of lipid accumulation, ATP depletion, and immobilization of the macrophage foam cells is likely to ultimately lead to their death. Of note, death of a foam cell is bound to liberation of its cytoplasmic cholesteryl ester droplets into the extracellular space, where the droplets mix with the preexisting extracellular lipid droplets.…”
Section: Development Of An Atheromamentioning
confidence: 99%